2022
DOI: 10.1038/s43856-022-00137-0
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of HLA genotype on the development of metal hypersensitivity following joint replacement

Abstract: Background Over five million joint replacements are performed across the world each year. Cobalt chrome (CoCr) components are used in most of these procedures. Some patients develop delayed-type hypersensitivity (DTH) responses to CoCr implants, resulting in tissue damage and revision surgery. DTH is unpredictable and genetic links have yet to be definitively established. Methods At a single site, we carried out an initial investigation to identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Phagocytic cells are hypothesized to engage in inflammatory cell induced corrosion. Recent studies link patient genotype to aseptic lymphocyte‐dominated vasculitis association lesion (ALVAL) susceptibility 60 . Improving fatigue performance in additively manufactured titanium alloys (particularly in β alloys) remains an ongoing issue.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytic cells are hypothesized to engage in inflammatory cell induced corrosion. Recent studies link patient genotype to aseptic lymphocyte‐dominated vasculitis association lesion (ALVAL) susceptibility 60 . Improving fatigue performance in additively manufactured titanium alloys (particularly in β alloys) remains an ongoing issue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of delayed type hypersensitivity (DTH) to metals may be complicated by different interpretation of the term "DTH" by allergists and surgeons. Langton et al reported in 2022 that variation in HLA class II phenotype influences susceptibility to DTH following implantation of MoM CoCr hip prosthesis (36).…”
Section: Discussionmentioning
confidence: 99%
“…Langton et al. reported in 2022 that variation in HLA class II phenotype influences susceptibility to DTH following implantation of MoM CoCr hip prosthesis ( 36 ). Patients who underwent revision of their MoM hip prosthesis had: assessment of metal ion concentration in blood, serum, joint fluid; assessment of explanted joint for volumetric wear; evaluation of periimplant tissue samples; HLA genotyping from buccal samples.…”
Section: Discussionmentioning
confidence: 99%
“…HLA sequencing showed that DQA1*02:01, DQB1*02:02 and DRB1*07:01 were significantly positive with ALVAL. Additionally, DQA1*02:01–DQB1*02:02 had the highest affinity binding to the N-terminal sequence of albumin, while DQA1*01:01–DQB1*05:01 exhibited the lowest binding affinity, which was found in patients without ALVAL in a high frequency ( 54 ). Another study showed that in patients with MoM bearings, CD86 and HLA-DR molecule expression on the surface of APCs is increased, strongly implying the presence of an immune response ( 55 ).…”
Section: Introductionmentioning
confidence: 98%
“…Although NTS is not the primary (or even secondary) binding site for Co 2+ , it still can in theory bind to Co 2+ if these are present at sufficiently high levels. Furthermore, patients with an HLA class II genotype that encodes a protein with peptide-binding grooves possessing greater affinity for the N-terminal sequence of HSA have a greater risk of developing delayed-type hypersensitivity ( 54 ). Therefore, although yet to be proven, cobalt–HSA complexes are considered to be potential immunogens which can elicit ALVAL ( 101 ).…”
Section: Introductionmentioning
confidence: 99%